Assessment of quality of sleep and its association with body mass index among medical consultants working in a medical college in northern India - Bathla, Manish (Indian J Psychiatry, 2020)
BACKGROUND: Medical specialist/consultants are exposed to various factors such as long duty hours, call duties, academics, meetings and regulation of departmental work which has adversely affected their sleep quality. OBJECTIVE: To assess sleep quality and association of body mass index with quality of sleep among medical consultants working in medical college. METHOD AND TOOL: This is a cross-sectional study and was done by convenient sampling technique. Pittsburg Sleep Quality Index (PSQI) was used as the assessment tool which categorizes sleep as good or poor according to the score. Chi-square test was applied to establish an association with the variables. RESULTS: A total of 67 responses were obtained, of which 28 showed good sleep on PSQI. Among consultants having good quality sleep, the majority were females (n=18); aged above 40 years (n=17). No relationship was seen with BMI and chronic disease. Consultants spending more than 85% of the time in bed sleeping (p< 0.006) and those going to bed before 10.30 pm (p<0.026) had good sleep quality. CONCLUSION: Good quality of sleep was observed in females, people above 40 years and those who don't have any chronic disease, though this association of sleep quality with the factors was not significant. Going to bed early (before 10:30 pm) had a positive effect on sleep quality (p<0.026). In general, poor sleep quality was seen among medical consultants.